Method of reconstructive surgery for damaged extrahepatic bile ducts: immediate and long-term results - A. B. Sidorenko; Y. I. Zakharov; Ya. G. Moysyuk (Трансплантология (Москва))
Background. Reconstructive surgery for iatrogenic injuries of the bile ducts involves the formation of a biliodigestive anastomosis. The development of anastomotic stricture is the most severe complication of this operation.Aim of the study. To evaluate the immediate and long-term results of treatment and follow-up of patients with iatrogenic injuries of the bile ducts who underwent reconstructive surgery on the bile ducts with additional creation of gastroenteroanastomosis.Material and methods. The study included 26 patients operated on according to the original method in the period 2010-2018.Results. In the study group, complications in the early postoperative period developed in 3 (11.5%) patients. Endoscopic interventions using the formed gastroenteroanastomosis in the long-term period were performed in 7 patients. The results of treatment were followed in 25 (96%) patients. The median follow-up period was 90 months [81.5;110] (42-129). Conclusion. The use of the proposed original technique of reconstructive surgery has demonstrated its effectiveness and safety, with the possibility of dynamic endoscopic control and, if necessary, the treatment of postoperative complications such as cholelithiasis and biliodigestive anastomosis strictures.